Examining the Factors Determining the Prevalence of Hiv/aids in Laroo Division, Gulu District - Triumph Lornah Lakica (Uganda Christian University, 2024)
This study sought to examine the factors determining the prevalence of HIV/AIDS prevalence in Laroo division Gulu District. The study was guided by three objectives that is to say to examine findings from the research to develop evidence-based recommendations for targeted interventions and policy strategies to reduce HIV/AIDS prevalence and improve health outcomes in Laroo Division. To examine behavioural risk factors such as sexual behaviour, substance use and condom use among different demographic groups within the community. And to examine the demographic factors that are at play in determining the continuous prevalence of HIV/AIDS in the division of Laroo. The study employed the Quantitative methods. The researcher used a sample size of 93 respondents and later used Statistical Package of Social Sciences (SPSS) to analyse the data. Results of the study shows that; socio-economic factors like poverty and education, behavioural factors like substance abuse and multiple sexual partners, demographic factors like age, gender and migration significantly contribute to HIV/AIDS prevalence. The study recommends the following; development of programmes to improve the socio-economic conditions, socio-economic interventions like poverty elevation and job creation to improve the socio-economic conditions. The study also recommends behavioural interventions like community-based initiatives to promote safe sexual practices and reduce substance abuse. The study finally recommends demographic specific strategies to address the specific needs of different age groups and genders.